Internet business: Its origins, theoretical issues and its applications - Gomez Alvarado, H. (2016)
Companies in the 21st century should adapt their business models so that they can operate via the Internet. Today, millions of transactions are performed on the Web at an ever-increasing pace. Moreover, potential of their commercial applications are innumerable. In this paper, we present a theoretical study of Internet business that rely on the concept of e-commerce and discuss the main e-strategies, namely those that provide users with a sense of security and confidence when doing buying and selling transactions, i.e. areas that can be improved by information technology. Also, the modern philosophy of seeking stellar products and in generating entire paradigms to sell them based on their unique characteristics implies that we should adopt measures to examine the growth of online businesses that involve inclusive-driven political policies and security, and which support the transition from physical to digital commerce.